1998
DOI: 10.1161/01.hyp.31.3.836
|View full text |Cite
|
Sign up to set email alerts
|

Human Vascular Renin-Angiotensin System and Its Functional Changes in Relation to Different Sodium Intakes

Abstract: A growing body of evidence supports the existence of a tissue-based renin-angiotensin system (RAS) in the vasculature, but the functional capacity of vascular RAS was not investigated in humans. In 28 normotensive healthy control subjects, the metabolism of angiotensins through vascular tissue was investigated in normal, low, and high sodium diets by the measurement of arterial-venous gradient of endogenous angiotensin (Ang) I and Ang II in two different vascular beds (forearm and leg), combined with the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…Preclinical studies have shown that high sodium intake increases several components of the intrarenal RAAS, including angiotensinogen (12), ACE activity (34), and Ang II (35). Accordingly, in humans, high sodium intake increased the peripheral vascular conversion of Ang I to Ang II, indicating an increase in tissue ACE activity (36). Increased renal ACE activity caused by high sodium intake combined with increased renin production caused by low vitamin D (24,37) may concertedly promote progression of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that high sodium intake increases several components of the intrarenal RAAS, including angiotensinogen (12), ACE activity (34), and Ang II (35). Accordingly, in humans, high sodium intake increased the peripheral vascular conversion of Ang I to Ang II, indicating an increase in tissue ACE activity (36). Increased renal ACE activity caused by high sodium intake combined with increased renin production caused by low vitamin D (24,37) may concertedly promote progression of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…On multivariate analysis we found that sodium intake also modified the effect of ACE genotype on AngI response, independent from AngII response. The mechanism underlying this interaction between sodium status, ACE genotype and AngI responsiveness may be related to effects of sodium status on tissue AngI conversion [28]. However, genotype-associated effects of differences in baseline values during the different sodium intakes might also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…26,[87][88][89] However, the majority of blacks with HTN do not have fully suppressed circulating renin levels, 90 and dietary salt-induced suppression of renin production and, thereby, circulating renin levels have been associated with higher, not lower, levels of vascular angiotensin II production. 91 Several reports have highlighted the significant overlap in BP responses of blacks and whites to monotherapy with ACE inhibitors and the finding that the variation of BP response is much larger within racial/ethnic groups than between them. 87,88 In addition, other studies of blacks and whites have suggested greater, not lesser, activation of the renal RAS in healthy blacks, 92 as well as a blunted suppression of intrarenal RAS activity in blacks compared with whites when consuming a high-sodium diet.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…93 This observation might also help explain why the largest racial differences in BP response during RAS blockade occur in the setting of a high dietary sodium intake; dietary sodium intake in salt-sensitive humans suppresses urinary NO metabolites 94,95 and augments vascular angiotensin II production. 91 Furthermore, the excessive rates of pressure-related target-organ injury in blacks with HTN (LVH, CKD, and proteinuria), as well as the high rates of obesity, have all been linked to RAS activation.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%